Exchange Rates and Trade Balance Adjustment in Emerging Market Economies. (Policy Papers; Policy Paper, 2006)
The paper finds that simple econometric specifications yield surprising rich and complex dynamics -- relative prices respond to the nominal exchange rate and pass-through effects, import and export volumes respond to relative price changes, and the trade balance responds to changes in import and export values.